AIDS policy formulation in the workplace and the economic cost of AIDS : a Western Cape survey 1992 - Crafford, Gabriel Johannes (Stellenbosch : Stellenbosch University, 2012)
Study project (M. Com.) -- University of Stellenbosch, 1993.